Membrane electrode, preparation method thereof and fuel cell

By using a gradient quaternized cathode bilayer catalytic layer structure, the problem of uneven phosphoric acid distribution in the HT-PEMFC membrane electrode was solved, achieving uniform phosphoric acid distribution and a highly efficient three-phase reaction interface, thereby improving the performance and stability of the fuel cell.

CN120955176APending Publication Date: 2025-11-14SHANGHAI INST OF SPACE POWER SOURCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510945314.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-09
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

In traditional HT-PEMFC membrane electrode assemblies, the uneven distribution of phosphoric acid in the cathode catalyst layer leads to excessive phosphoric acid covering or lack of phosphoric acid on the platinum-based catalyst, affecting proton conduction capacity and the construction of the three-phase reaction interface, thus reducing catalyst utilization and fuel cell performance.

Method used

A gradient quaternization cathode bilayer catalytic layer structure is adopted. The first catalytic layer has a high density of quaternary ammonium groups on the side close to the proton exchange membrane, while the second catalytic layer has a low density of quaternary ammonium groups on the side far from the proton exchange membrane. The distribution of phosphoric acid is regulated by electrostatic interaction and ion pair interaction to prevent excessive diffusion or loss of phosphoric acid, thereby constructing a smooth proton transport path and an efficient three-phase reaction interface.

Benefits of technology

Effective regulation of phosphoric acid distribution improves the utilization rate of platinum-based catalysts, reduces energy loss, and enhances the output power and lifespan of fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120955176A_ABST
    Figure CN120955176A_ABST
Patent Text Reader

Abstract

The invention discloses a membrane electrode, a preparation method thereof and a fuel cell. The membrane electrode comprises an anode gas diffusion electrode, a proton exchange membrane and a cathode gas diffusion electrode which are sequentially arranged, the cathode gas diffusion electrode comprises a first catalyst layer and a second catalyst layer; the first catalyst layer is arranged on one side close to the proton exchange membrane; each of the first catalyst layer and the second catalyst layer comprises quaternized polybenzimidazole, a platinum-based catalyst and polytetrafluoroethylene; wherein the quaternary ammonium group grafting degree of the quaternized polybenzimidazole in the first catalyst layer is greater than the quaternary ammonium group grafting degree of the quaternized polybenzimidazole in the second catalyst layer. According to the membrane electrode disclosed by the invention, the distribution of phosphoric acid in a cathode catalyst layer is regulated and controlled through a gradient quaternized cathode double-layer catalyst layer structure, and an efficient proton transmission channel and a three-phase reaction interface are favorably constructed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fuel cell technology, and in particular to a membrane electrode, its preparation method, and a fuel cell. Background Technology

[0002] Fuel cells, as a highly efficient and clean energy conversion device, have attracted widespread attention. Among them, high-temperature proton exchange membrane fuel cells (HT-PEMFCs) have broad application prospects in distributed power generation, portable power supplies, and vehicle power supplies due to their advantages such as high operating temperature (typically 120℃~200℃), strong tolerance to impurities such as CO, simplified system, and easy thermal management.

[0003] In HT-PEMFC, the membrane electrode assembly (MEA) is the core component, and its performance directly determines the overall performance of the fuel cell. A traditional HT-PEMFC MEA typically consists of an anode gas diffusion layer, an anode catalyst layer, a proton exchange membrane (PEM), a cathode catalyst layer, and a cathode gas diffusion layer. The PEM often uses a phosphoric acid-doped polybenzimidazole membrane, and the catalyst layer is usually composed of a platinum-based catalyst, a polymer binder, and polytetrafluoroethylene (PTFE). During MEA assembly, some phosphoric acid permeates from the PEM into the anode and cathode catalyst layers via a hot-pressing process, becoming the core medium for proton conduction in the catalyst layer. This allows for the construction of a three-phase reaction interface within the catalyst layer, involving the reactant gas, the platinum-based catalyst, and protons.

[0004] In HT-PEMFCs, the cathode reaction (oxygen reduction reaction) is the rate-determining step of the fuel cell reaction. Due to its slow kinetics, the cathode reaction is highly sensitive to the distribution of phosphoric acid within the catalyst layer compared to the anode reaction. However, traditional HT-PEMFC membrane electrode assemblies suffer from uneven phosphoric acid distribution within the cathode catalyst layer.

[0005] Under high-temperature operating conditions, phosphoric acid exhibits increased fluidity. On one hand, phosphoric acid in the proton exchange membrane (PEMFC) tends to migrate outwards, excessively accumulating in the region of the catalyst layer near the PEMFC. This results in excessive phosphoric acid covering the platinum-based catalyst in the catalyst layer surrounding the PEMFC, poisoning the active sites of the platinum-based catalyst. On the other hand, regions of the catalyst layer far from the PEMFC are prone to phosphoric acid loss, leading to a lack of phosphoric acid and a decrease in proton conductivity, significantly reducing the efficiency of the three-phase reaction interface construction. This uneven distribution of phosphoric acid in the catalyst layer severely restricts the catalyst utilization rate, thereby affecting the stable power output and lifespan of the HT-PEMFC.

[0006] Therefore, developing a membrane electrode structure and preparation method that can effectively regulate the distribution of phosphoric acid is of great significance for improving the overall performance of HT-PEMFC.

[0007] The statements herein provide only background information in relation to this invention and do not necessarily constitute prior art. Summary of the Invention

[0008] The purpose of this invention is to provide a membrane electrode that solves the problem of uneven distribution of phosphoric acid in the cathode catalytic layer of the HT-PEMFC membrane electrode. The aim is to regulate the distribution of phosphoric acid in the cathode catalytic layer by using a gradient quaternized cathode bilayer catalytic layer structure (including a first catalytic layer and a second catalytic layer).

[0009] To achieve the above objectives, the present invention provides a membrane electrode comprising an anode gas diffusion electrode, a proton exchange membrane, and a cathode gas diffusion electrode arranged sequentially.

[0010] The cathode gas diffusion electrode includes a first catalyst layer and a second catalyst layer; the first catalyst layer is disposed on the side close to the proton exchange membrane; both the first catalyst layer and the second catalyst layer include quaternized polybenzimidazole, a platinum-based catalyst, and polytetrafluoroethylene; wherein, the quaternary ammonium group grafting degree of the quaternized polybenzimidazole in the first catalyst layer is greater than that in the second catalyst layer.

[0011] Optionally, the quaternary ammonium group grafting degree of the quaternized polybenzimidazole in the first catalyst layer is 60% to 100%; and the quaternary ammonium group grafting degree of the quaternized polybenzimidazole in the second catalyst layer is 0% to 40%.

[0012] Optionally, the structure formed by the quaternized polybenzimidazole is as follows:

[0013] The value of n ranges from 60000 to 80000.

[0014] Optionally, the total amount of the quaternized polybenzimidazole and polytetrafluoroethylene is 10% to 20% of the mass percentage of the platinum-based catalyst.

[0015] Optionally, the mass ratio of the quaternized polybenzimidazole to the polytetrafluoroethylene is 1:3 to 3:1.

[0016] Optionally, the proton exchange membrane is a phosphate-doped polybenzimidazole membrane, with a phosphate doping amount of 200% to 400% by mass.

[0017] The present invention also provides a method for preparing the above-mentioned membrane electrode, characterized in that it comprises:

[0018] Step 1: Provide a cathode gas diffusion layer, an anode gas diffusion electrode, and a proton exchange membrane;

[0019] Step 2: Linear aryl ether polybenzimidazole and glycidyltrimethylammonium chloride are dissolved and mixed in a first ratio, and then heated to react and obtain a first solution; linear aryl ether polybenzimidazole and glycidyltrimethylammonium chloride are dissolved and mixed in a second ratio, and then heated to react and obtain a second solution; both the first and second solutions contain quaternized polybenzimidazole, the quaternary ammonium group grafting degree of the quaternized polybenzimidazole in the first solution is 60% to 100%; the quaternary ammonium group grafting degree of the quaternized polybenzimidazole in the second solution is 0% to 40%;

[0020] Step 3: Dissolve and mix polytetrafluoroethylene, surfactant, and platinum-based catalyst to obtain a dispersion;

[0021] Step 4: Add the dispersion to the first solution to obtain a first catalyst layer slurry; add the dispersion to the second solution to obtain a second catalyst layer slurry;

[0022] Step 5: Spray the second catalyst layer slurry onto the surface of the cathode gas diffusion layer to form the second catalyst layer, and spray the first catalyst layer slurry onto the surface of the second catalyst layer to form the first catalyst layer, thereby preparing the cathode gas diffusion electrode;

[0023] Step 6: The cathode gas diffusion electrode, the proton exchange membrane, and the anode gas diffusion electrode are stacked sequentially, and the membrane electrode is fabricated by hot pressing.

[0024] Optionally, in step 2, the first ratio is: the molar ratio of linear aryl ether polybenzimidazole to glycidyl trimethylammonium chloride is 1:0.6 to 1:1; the second ratio is: the molar ratio of linear aryl ether polybenzimidazole to glycidyl trimethylammonium chloride is 1:0 to 1:0.4.

[0025] Optionally, in step 2, the temperature of the heating reaction is 80℃~100℃, and the reaction time is 10h~15h.

[0026] The present invention also provides a fuel cell comprising the membrane electrode assembly as described above. The present invention further provides a fuel cell characterized in that it comprises the membrane electrode assembly described above.

[0027] Compared with the prior art, the beneficial effects of the technical solution of the present invention include at least the following:

[0028] In the membrane electrode of this invention, the distribution of phosphoric acid in the cathode catalyst layer is effectively controlled through a gradient quaternized cathode bilayer catalyst layer structure (comprising a first catalyst layer and a second catalyst layer). On one hand, the first catalyst layer (near the proton exchange membrane) of this invention introduces a high density of quaternized ammonium groups through quaternized polybenzimidazole (denoted as QAPBI). This high density of quaternized ammonium groups provides a large number of positive charge sites, effectively immobilizing negatively charged phosphate ions (H₂PO₄) through strong electrostatic interactions. - The phosphoric acid (phosphoric acid) forms stable ion pairs (e.g., H3PO4), preventing excess phosphoric acid from freely diffusing to the surface of the platinum-based catalyst in the first catalyst layer and poisoning it, thus reducing the phosphoric acid poisoning effect. On the other hand, a certain amount of quaternary ammonium groups are introduced into the second catalyst layer (away from the proton exchange membrane) using QAPBI. Through moderate ion pairing, the phosphoric acid content of the second catalyst layer is stabilized. Simultaneously, because QAPBI itself has a dense structure, the relatively low grafting degree of quaternary ammonium groups in the second catalyst layer prevents the formation of a dense microstructure that would block gas diffusion channels and avoids excessively high interfacial impedance between the second catalyst layer and adjacent layers (gas diffusion layer, first catalyst layer). Therefore, the gradient quaternized cathode catalyst layer provides a smooth transport path for protons and gases and reduces the phosphoric acid poisoning effect, which is beneficial for constructing a continuous and efficient three-phase reaction interface, improving the utilization rate of the platinum-based catalyst, and thus reducing the energy loss of HT-PEMFC. Attached Figure Description

[0029] Figure 1 This is a schematic diagram of the structure of a membrane electrode according to the present invention.

[0030] Figure 2 This is a process flow diagram of a method for preparing a membrane electrode according to the present invention.

[0031] Figure 3 The polarization characteristic curves are for the membrane electrodes of Examples 1-3 and the comparative examples.

[0032] Figure 4 Impedance spectra of the membrane electrodes of Examples 1-3 and the comparative examples are shown.

[0033] Figure 5 The cyclic voltammetry curves are for the membrane electrodes of Examples 1-3 and the comparative examples.

[0034] Explanation of reference numerals in the attached diagram:

[0035] Anode gas diffusion electrode 10

[0036] Proton exchange membrane 20

[0037] Cathode gas diffusion electrode 30

[0038] Cathode catalyst layer 31

[0039] First catalyst layer 311

[0040] Second catalyst layer 312

[0041] Cathode gas diffusion layer 32 Detailed Implementation

[0042] The following detailed description, in conjunction with the accompanying drawings and specific embodiments, provides a further detailed explanation of the membrane electrode, its preparation method, and the fuel cell proposed in this invention. The advantages and features of this invention will become clearer from the following description. It should be noted that the drawings are in a very simplified form and use non-precise proportions, used only to facilitate and clarify the illustration of the embodiments of this invention. Please refer to the drawings to make the objectives, features, and advantages of this invention more apparent and understandable. It should be understood that the structures, proportions, sizes, etc., depicted in the accompanying drawings are only for illustrative purposes to aid those skilled in the art and are not intended to limit the implementation conditions of this invention. Therefore, they have no substantial technical significance. Any modifications to the structure, changes in proportions, or adjustments to the size, without affecting the effects and objectives achieved by this invention, should still fall within the scope of the technical content disclosed in this invention.

[0043] The "quaternary ammonium group grafting degree" mentioned in this article refers to the proportion of polybenzimidazole polymer chains chemically grafted with quaternary ammonium groups. For example, if the quaternary ammonium group grafting degree of quaternized polybenzimidazole is 80%, it means that in the polybenzimidazole polymer chain, 80% of the reactive active sites have been chemically grafted with quaternary ammonium groups (-N). + (CH3)3Cl-). The quaternary ammonium group grafting degree of 0% in the quaternized polybenzimidazole described in this article means that the polybenzimidazole polymer chain has not undergone quaternization treatment, that is, the polybenzimidazole polymer chain has not been grafted with quaternary ammonium groups.

[0044] As described in the background section, the uneven distribution of phosphoric acid in the catalytic layer of a traditional membrane electrode results in excessive phosphoric acid covering the platinum-based catalyst in the region near the proton exchange membrane, while the region far from the proton exchange membrane lacks phosphoric acid, leading to an ineffective three-phase reaction interface and reduced catalyst utilization. Furthermore, due to the slow kinetics of the cathode reaction, its sensitivity to the distribution of phosphoric acid within the catalytic layer is significantly higher than that of the anolyte reaction, making it more susceptible to electrochemical reactions failing due to uneven distribution of phosphoric acid within the cathode catalytic layer.

[0045] To address the aforementioned issues, this invention provides a membrane electrode with a gradient quaternized cathode catalyst layer. Utilizing a bilayer catalyst layer structure (a first catalyst layer and a second catalyst layer) with varying degrees of quaternary ammonium group grafting, the distribution of phosphoric acid in the cathode catalyst layer can be controlled, thereby improving catalyst utilization, increasing fuel cell output power, and extending fuel cell lifespan. Quaternary ammonium groups can anchor phosphoric acid through ion-pair interactions. On one hand, the first catalyst layer (closer to the proton exchange membrane side) with a high degree of quaternary ammonium group grafting can effectively anchor a large amount of phosphoric acid using its high internal density of quaternary ammonium groups, inhibiting the free diffusion of phosphoric acid to the platinum-based catalyst surface, thus reducing the poisoning effect of phosphoric acid on the platinum-based catalyst. On the other hand, the second catalyst layer (far from the proton exchange membrane side) with a low degree of quaternary ammonium group grafting can stabilize the phosphoric acid content through its lower internal density of quaternary ammonium groups, while avoiding excessively dense microstructure within the second catalyst layer that could lead to blocked gas diffusion channels or excessive interfacial impedance with adjacent functional layers. This facilitates the construction of efficient proton transport channels and a three-phase reaction interface.

[0046] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments.

[0047] like Figure 1 As shown, the present invention provides a membrane electrode comprising an anode gas diffusion electrode 10, a proton exchange membrane 20, and a cathode gas diffusion electrode 30 arranged sequentially. The anode gas diffusion electrode 10 includes an anode catalyst layer (not shown) and an anode gas diffusion layer (not shown). The cathode gas diffusion electrode 30 includes a cathode catalyst layer 31 and a cathode gas diffusion layer 32. The cathode catalyst layer 31 includes a first catalyst layer 311 and a second catalyst layer 312. The first catalyst layer 311 is disposed near the proton exchange membrane 20; the second catalyst layer 312 is disposed away from the proton exchange membrane 20, that is, the second catalyst layer 312 is disposed between the cathode gas diffusion layer 32 and the first catalyst layer 311.

[0048] Both the first catalyst layer 311 and the second catalyst layer 312 contain quaternized polybenzimidazole, a platinum-based catalyst, and polytetrafluoroethylene (PTFE). The quaternized polybenzimidazole serves as an ionomer within the catalyst layer, providing mechanical strength and proton conductivity. The platinum-based catalyst provides active sites for the electrochemical reaction. The PTFE exhibits strong hydrophobicity, forming a continuous hydrophobic network within the catalyst layer to ensure oxygen transport. Furthermore, the PTFE acts as a binder, bonding the catalyst particles to the ionomer (quaternized polybenzimidazole) into a cohesive whole.

[0049] In this invention, the grafting degree of quaternary ammonium groups of quaternized polybenzimidazole in the first catalyst layer 311 is greater than that in the second catalyst layer 312, and the first catalyst layer 311 and the second catalyst layer 312 form a gradient quaternized cathode catalyst layer 31. In some embodiments, the grafting degree of quaternary ammonium groups of quaternized polybenzimidazole in the first catalyst layer 311 is 60% to 100%; and the grafting degree of quaternary ammonium groups of quaternized polybenzimidazole in the second catalyst layer 312 is 0% to 40%. The gradient quaternized cathode catalyst layer 31 in this invention plays at least the following role:

[0050] (1) Because the first catalyst layer 311 is close to the proton exchange membrane 20, and the phosphoric acid in the proton exchange membrane 20 easily migrates to the nearby catalyst layer, it is easy for phosphoric acid to accumulate in the first catalyst layer 311 and cover the platinum-based catalyst. Therefore, in order to improve this defect, the present invention introduces a high density of quaternary ammonium groups into the first catalyst layer 311. The quaternary ammonium groups provide a large number of positive charge sites, which attract phosphate ions (H2PO4) through electrostatic attraction. - / HPO4 2- Strong ion pair interactions are generated between the two, forming stable ion pairs that effectively anchor a large amount of phosphoric acid. This prevents phosphoric acid from freely diffusing and excessively agglomerating and covering the surface of the platinum-based catalyst, thus avoiding the poisoning effect of phosphoric acid on the platinum-based catalyst and improving the utilization rate of the platinum-based catalyst.

[0051] (2) In this invention, a quaternary ammonium group with a low grafting degree is introduced into the second catalyst layer 312, so that part of the phosphoric acid is anchored in the second catalyst layer 312 through its appropriate ion pair interaction, thereby maintaining the phosphoric acid content in the second catalyst layer 312 and avoiding excessive loss of phosphoric acid in the second catalyst layer 312. This avoids the risk that the three-phase reaction interface cannot be constructed in the region of the cathode catalyst layer 31 far from the proton exchange membrane 20. At the same time, since in the quaternized polybenzimidazole, an excess of quaternary ammonium groups will increase the charge density on the polybenzimidazole main chain, and adjacent groups will be tightly packed through ionic bonds or hydrogen bonds, restricting the stretching of the molecular chain and resulting in a denser structure, the quaternary ammonium group with a low grafting degree effectively prevents the microstructure in the second catalyst layer 312 from being too dense, which would affect gas transport and the interfacial impedance in the catalyst layer.

[0052] Therefore, the different quaternary ammonium groups grafted into the first catalyst layer 311 and the second catalyst layer 312 are conducive to achieving a uniform distribution of phosphoric acid, thereby constructing a smooth transport path for protons, efficiently constructing a three-phase reaction interface, which is beneficial to reducing the ohmic impedance of the membrane electrode and thus reducing the energy loss of HT-PEMFC.

[0053] In some embodiments, the quaternized polybenzimidazole (QAPBI) has the following structure:

[0054]

[0055] Where n ranges from 60,000 to 80,000. This quaternized polybenzimidazole structure exhibits good chemical stability and can react with phosphate (H₂PO₄)⁻. - / HPO4 2- Ion pairs interact between the molecules, anchoring phosphoric acid and thus giving it good ionic conductivity, making it suitable as an ionomer for use as a catalyst layer.

[0056] In some embodiments, the total amount of the quaternized polybenzimidazole and polytetrafluoroethylene is 10% to 20% of the mass percentage of the platinum-based catalyst. This ratio ensures sufficient ionomers and binders in the catalyst layer, while also ensuring a moderate loading of the platinum-based catalyst, which is beneficial to the stability and catalytic activity of the membrane electrode.

[0057] In some embodiments, the mass ratio of the quaternized polybenzimidazole to the polytetrafluoroethylene is 1:3 to 3:1.

[0058] In some embodiments, the platinum-based catalyst in the cathode catalyst layer 31 is a carbon-supported platinum-cobalt catalyst (PtCo / C catalyst), and the loading of the noble metal platinum (Pt) is 0.4 mg / cm³. 2 ~0.6mg / cm 2 .

[0059] In some embodiments, the proton exchange membrane 20 is a phosphate-doped polybenzimidazole membrane with a phosphate doping amount of 200% to 400% by mass; the thickness of the phosphate-doped polybenzimidazole membrane is 10 μm to 40 μm. Phosphate-doped polybenzimidazole membranes exhibit good high-temperature proton conductivity and are suitable for application in HT-PEMFCs.

[0060] In some embodiments, in the anode gas diffusion electrode 10, the anode gas diffusion layer includes an anode support layer and an anode microporous layer; the anode support layer is carbon paper or carbon cloth, and the anode microporous layer contains carbon powder and polytetrafluoroethylene (PTFE), wherein the mass percentage of PTFE in the anode microporous layer is 10% to 30%. The anode catalyst layer includes an anode catalyst and PTFE, wherein the anode catalyst is a carbon-supported platinum catalyst (Pt / C catalyst), and the loading of the noble metal Pt is 0.1 mg / cm³. 2 ~0.3mg / cm 2 The mass percentage of polytetrafluoroethylene is 10% to 30%.

[0061] In some embodiments, in the cathode gas diffusion electrode 10, the cathode gas diffusion layer 32 includes a cathode support layer and a cathode microporous layer; the cathode support layer is carbon paper or carbon cloth, and the cathode microporous layer contains carbon powder and polytetrafluoroethylene, wherein the mass percentage of polytetrafluoroethylene in the cathode microporous layer is 10% to 30%.

[0062] like Figure 2 As shown, the present invention also provides a method for preparing the above-mentioned membrane electrode, comprising:

[0063] Step 1: Provide a cathode gas diffusion layer, an anode gas diffusion electrode, and a proton exchange membrane.

[0064] The anode gas diffusion electrode comprises an anode gas diffusion layer and an anode catalyst layer. In some embodiments, the cathode gas diffusion layer and the anode gas diffusion layer are prepared by the same method, comprising: mixing carbon powder and PTFE emulsion, adding an appropriate amount of ethanol, ultrasonically stirring to obtain a slurry, coating the slurry onto the surface of carbon paper, and then determining the carbon powder loading and PTFE content by weighing. The carbon paper is placed in a muffle furnace and heat-treated at above 300°C for 30 min to 1 h, and then cooled to room temperature to obtain the cathode gas diffusion layer or the anode gas diffusion layer. The carbon paper forms a support layer, and a microporous layer is formed on the side of the carbon paper coated with carbon powder and PTFE.

[0065] In some embodiments, the preparation method of the anode gas diffusion electrode includes: weighing a Pt / C catalyst, adding a small amount of deionized water to wet it, stirring and dispersing it evenly, then adding a PTFE aqueous alcohol solution, and ultrasonically dispersing it evenly to obtain an anode catalyst slurry. The anode catalyst slurry is then uniformly coated onto the microporous surface of the anode gas diffusion layer using an ultrasonic spraying method.

[0066] In some embodiments, the method for preparing the proton exchange membrane includes: cutting the PBI membrane to a certain size, immersing the cut PBI membrane in 85 wt.% phosphoric acid at 120°C, blotting off excess phosphoric acid from the surface of the PBI membrane with filter paper, weighing the membrane, and calculating the phosphoric acid doping amount of the proton exchange membrane. The phosphoric acid doping amount of the proton exchange membrane is assessed using the mass ratio of phosphoric acid to resin (mass of doped phosphoric acid / original mass of the PBI membrane). The immersion process is repeated until the phosphoric acid doping amount reaches 200%–400%, expressed as a mass percentage.

[0067] Step 2: Linear aryl ether polybenzimidazole and glycidyltrimethylammonium chloride are dissolved and mixed in a first ratio, and then heated to react and obtain a first solution; linear aryl ether polybenzimidazole and glycidyltrimethylammonium chloride are dissolved and mixed in a second ratio, and then heated to react and obtain a second solution; both the first solution and the second solution contain quaternized polybenzimidazole, the quaternary ammonium group grafting degree of the quaternized polybenzimidazole in the first solution is 60% to 100%; the quaternary ammonium group grafting degree of the quaternized polybenzimidazole in the second solution is 0% to 40%.

[0068] The structure of the linear aryl ether polybenzimidazole (denoted as OPBI) is as follows:

[0069] The value of is in the range of 60000 to 80000.

[0070] The structure of the glycidyl trimethyl ammonium chloride (GTMAC) is as follows:

[0071]

[0072] The two react upon heating to form quaternized polybenzimidazole (QAPBI), with the following structure:

[0073] The value of n ranges from 60000 to 80000.

[0074] The first ratio is a molar ratio of linear aryl ether polybenzimidazole to glycidyltrimethylammonium chloride of 1:0.6 to 1:1; the second ratio is a molar ratio of linear aryl ether polybenzimidazole to glycidyltrimethylammonium chloride of 1:0 to 1:0.4. For example, when the molar ratio of linear aryl ether polybenzimidazole to glycidyltrimethylammonium chloride is 1:0.6, the grafting degree of quaternary ammonium groups in the quaternized polybenzimidazole in the final first catalyst layer is 60%. When the molar ratio of linear aryl ether polybenzimidazole to glycidyltrimethylammonium chloride is 1:0, it indicates that glycidyltrimethylammonium chloride was not added to the second solution, that is, the grafting degree of quaternary ammonium groups in the quaternized polybenzimidazole in the final second catalyst layer is 0%.

[0075] In some embodiments, the heating reaction is carried out at a temperature of 80°C to 100°C for a reaction time of 10 to 15 hours.

[0076] In some embodiments, the solvent for dissolving OPBI and GTMAC is dimethyl sulfoxide.

[0077] Step 3: Dissolve and mix polytetrafluoroethylene, surfactant, and platinum-based catalyst to obtain a dispersion.

[0078] In some embodiments, step 3 includes:

[0079] Step 3.1: Disperse PTFE in deionized water, dissolve the surfactant in dimethyl sulfoxide, and mix the two to obtain the first dispersion;

[0080] Step 3.2: Disperse the PtCo / C catalyst in dimethyl sulfoxide to obtain a second dispersion;

[0081] Step 3.3: Mix the first dispersion and the second dispersion to obtain the dispersion.

[0082] As an example, the surfactant is FC-4430, purchased from 3M Company, USA.

[0083] Step 4: Add the dispersion to the first solution to obtain the first catalyst layer slurry; add the dispersion to the second solution to obtain the second catalyst layer slurry.

[0084] Step 5: Spray the second catalyst layer slurry onto the surface of the cathode gas diffusion layer to form the second catalyst layer, and spray the first catalyst layer slurry onto the surface of the first catalyst layer to form the first catalyst layer, thereby preparing the cathode gas diffusion electrode.

[0085] In this embodiment, the second catalyst layer slurry is sprayed onto the surface of the microporous layer of the cathode gas diffusion layer. In some embodiments, ultrasonic spraying is used to spray the first catalyst layer slurry and the second catalyst layer slurry.

[0086] Step 6: The cathode gas diffusion electrode, the proton exchange membrane, and the anode gas diffusion electrode are stacked sequentially, and the membrane electrode is fabricated by hot pressing.

[0087] During the stacking process, the first catalytic layer in the cathode gas diffusion electrode faces the proton exchange membrane, and the anode catalytic layer in the anode gas diffusion electrode faces the proton exchange membrane.

[0088] Example 1

[0089] This embodiment provides a method for preparing a membrane electrode containing a gradient quaternized cathode catalytic layer, comprising the following steps:

[0090] Step S1: Preparation of the cathode gas diffusion layer and the anode gas diffusion layer: Vulcan XC-72 carbon powder and PTFE emulsion are mixed, and an appropriate amount of ethanol is added. The mixture is ultrasonically stirred to obtain a slurry. This slurry is coated onto the surface of commercial Torray carbon paper, and the carbon powder loading and PTFE content are determined by weighing. The carbon paper is placed in a muffle furnace and heat-treated at 340°C for 30 minutes. After cooling to room temperature, the cathode gas diffusion layer is obtained. The anode gas diffusion layer is prepared using the same method.

[0091] The cathode gas diffusion layer and anode gas diffusion layer prepared in step S1 have the same composition and structure, both consisting of a support layer and a microporous layer. The support layer is Torray carbon paper with a thickness of 150 μm; the microporous layer contains Vulcan XC-72 toner and PTFE, with a Vulcan XC-72 toner loading of 2 mg / cm³. 2 The mass percentage of PTFE in the microporous layer is 30%, and the thickness of the microporous layer is 30 μm.

[0092] Step S2, Preparation of the anode gas diffusion electrode: Weigh 30% Pt / C catalyst, add a small amount of deionized water to wet and stir to disperse evenly, then add PTFE aqueous alcohol solution, and ultrasonically disperse evenly to obtain an anode catalyst slurry; the above slurry is uniformly coated onto the microporous layer surface of the anode diffusion layer using an ultrasonic spraying method to form an anode catalyst layer. The 30% Pt / C catalyst refers to the catalyst in which the mass of Pt accounts for 50% of the total mass of Pt and C support.

[0093] In the anode gas diffusion electrode prepared by step S2, the mass percentage of PTFE in the anode catalyst layer is 20%, and the Pt loading is 0.3 mg / cm³. 2 .

[0094] Step S3, prepare the cathode gas diffusion electrode:

[0095] Step S3.1, preparing the first catalyst layer slurry: Linear aryl ether polybenzimidazole (OPBI) is dissolved in dimethyl sulfoxide at 60°C, and glycidyltrimethylammonium chloride is added. The molar ratio of the linear aryl ether polybenzimidazole to the glycidyltrimethylammonium chloride is 1:0.8. The reaction is carried out at 90°C for 12 hours to obtain a first solution. In the first solution, the quaternary ammonium group grafting degree of the quaternized polybenzimidazole is 80%, and the mass fraction of the quaternized polybenzimidazole in the first solution is 1%. A certain amount of PTFE is dispersed in deionized water, and a certain amount of surfactant FC-4430 is dissolved in dimethyl sulfoxide. The PTFE solution and the FC-4430 solution are mixed to obtain a first dispersion. 50% PtCo / C catalyst is dispersed in dimethyl sulfoxide to obtain a second dispersion. The first dispersion and the second dispersion are added to the first solution to obtain the first catalyst layer slurry.

[0096] Step S3.2, Preparation of the second catalyst layer slurry: In this embodiment, the preparation method of the second catalyst layer slurry differs from that of the first catalyst layer slurry in that glycidyltrimethylammonium chloride is not added. That is, the molar ratio of the linear aryl ether polybenzimidazole to the glycidyltrimethylammonium chloride is 1:0, and the grafting degree of the quaternary ammonium groups of the quaternized polybenzimidazole in the obtained second catalyst layer slurry is 0%.

[0097] Step S3.3: Using ultrasonic spraying, the second catalyst layer slurry is sprayed onto the surface of the microporous layer of the cathode gas diffusion layer and dried at 80°C for 1 hour to form the second catalyst layer. The first catalyst layer slurry is then sprayed onto the surface of the first catalyst layer and dried at 80°C for 1 hour to form the first catalyst layer, thus preparing the cathode gas diffusion electrode.

[0098] The Pt loading in the cathode gas diffusion electrode prepared in step S3 is 0.6 mg / cm³. 2 The total amount of QAPBI and PTFE is 20% of the mass percentage of the 50% PtCo / C catalyst, and the mass ratio of QAPBI to PTFE is 1:3.

[0099] Step S4, preparation of the proton exchange membrane: First, cut the dried PBI membrane to a certain size. Place the cut PBI membrane in 85 wt.% phosphoric acid and immerse it at 120°C for 60 min. Blot off excess phosphoric acid from the surface of the PBI membrane with filter paper, weigh it quickly, and calculate the phosphoric acid doping amount of the PBI membrane. The phosphoric acid doping amount of the proton exchange membrane is examined using the mass ratio of phosphoric acid to resin (mass of doped phosphoric acid / original mass of PBI membrane). Repeat the immersion operation until the phosphoric acid doping amount reaches 400%, expressed as a mass percentage.

[0100] Step S5, hot pressing to fabricate the membrane electrode: The cathode gas diffusion electrode, the proton exchange membrane, and the anode gas diffusion electrode are stacked sequentially and placed in a hot press. The press is then heated at 160°C for 6 minutes to obtain the formed membrane electrode. This membrane electrode is then placed in a constant temperature and humidity chamber for storage. During the stacking process, the first catalytic layer of the cathode gas diffusion electrode faces the proton exchange membrane, and the anodic catalytic layer of the anode gas diffusion electrode faces the proton exchange membrane.

[0101] The active area of ​​the membrane electrode prepared by steps S1 to S5 is 4 cm². 2 .

[0102] Example 2

[0103] The difference between this embodiment and Embodiment 1 is that, in step S3.2, linear aryl ether polybenzimidazole and glycidyl trimethylammonium chloride are added, and the molar ratio of the linear aryl ether polybenzimidazole to the glycidyl trimethylammonium chloride is 1:0.2.

[0104] In the cathode gas diffusion electrode obtained in this embodiment, the grafting degree of quaternary ammonium groups of QAPBI in the first catalyst layer is 80%, and the grafting degree of quaternary ammonium groups of QAPBI in the second catalyst layer is 20%.

[0105] Example 3

[0106] The difference between this embodiment and Embodiment 1 is that, in step S3.2, linear aryl ether polybenzimidazole and glycidyl trimethylammonium chloride are added, and the molar ratio of the linear aryl ether polybenzimidazole to the glycidyl trimethylammonium chloride is 1:0.4.

[0107] In the cathode gas diffusion electrode obtained in this embodiment, the grafting degree of quaternary ammonium groups of QAPBI in the first catalyst layer is 80%, and the grafting degree of quaternary ammonium groups of QAPBI in the second catalyst layer is 40%.

[0108] Comparative Example

[0109] This comparative example provides a method for preparing a membrane electrode containing a conventional cathode catalyst layer, which differs from Example 1 in that:

[0110] Step S3: Prepare the cathode gas diffusion electrode:

[0111] Step S3.1, preparing the catalyst layer slurry: a certain amount of PTFE is dispersed in deionized water, a certain amount of surfactant FC-4430 is dissolved in dimethyl sulfoxide, and the PTFE solution and FC-4430 solution are mixed to obtain a first dispersion; 50% PtCo / C catalyst is dispersed in dimethyl sulfoxide to obtain a second dispersion, and the first dispersion and the second dispersion are mixed uniformly to obtain the catalyst layer slurry.

[0112] Step S3.2: The catalyst layer slurry is sprayed onto the microporous surface of the cathode gas diffusion layer using ultrasonic spraying, and dried at 80°C for 1 hour to form a cathode catalyst layer, thus preparing a cathode gas diffusion electrode.

[0113] In the cathode gas diffusion electrode obtained in this comparative example, the PTFE content in the cathode catalyst layer is 15% of the mass percentage of the 50% PtCo / C catalyst.

[0114] Referring to GB / T 20042.5-2009, the membrane electrodes obtained in Examples 1 to 3 and the comparative examples were used to fabricate fuel cells and their polarization curves were tested. The specific operating conditions were as follows: the single cell operating temperature was 160°C, the anode was fed with pure hydrogen gas, the cathode was fed with oxygen gas at atmospheric pressure, and the cathode to anode feed ratio was 1:1.

[0115] According to GB / T 20042.5-2009, the membrane electrodes obtained in Examples 1 to 3 and the comparative examples were used to make fuel cells for cyclic voltammetry testing. The specific operating conditions were as follows: the single cell operating temperature was 160°C, the anode was fed with pure hydrogen gas, the cathode was fed with nitrogen gas at atmospheric pressure, and the cathode to anode feed ratio was 1:1.

[0116] According to GB / T 20042.5-2009, the membrane electrode assemblies obtained in Examples 1-3 and the comparative example were used to fabricate fuel cells for impedance testing. The specific operating conditions were: single-cell operating temperature of 160℃, anode feed of pure hydrogen, cathode feed of atmospheric pressure oxygen, and a cathode-to-anode feed ratio of 1:1. The discharge current density was 0.5 A / cm². 2 .

[0117] See Figure 3 The polarization characteristic curves of the membrane electrodes prepared in Examples 1, 2, and 3 of the present invention and the comparative examples were measured. Figure 1 It can be seen that at 0.1 A / cm 2 The membrane electrode voltages for Examples 1, 2, 3, and the comparative example of the present invention were measured to be 0.724V, 0.728V, 0.721V, and 0.725V, respectively. The fuel cell power densities for Examples 1, 2, 3, and the comparative example of the present invention were measured to be 72.4 mW / cm². 2 72.8mW / cm 2 72.1mW / cm 2 72.5mW / cm 2 At 0.5A / cm 2The membrane electrode voltages for Examples 1, 2, 3, and the Comparative Example of the present invention were measured to be 0.602V, 0.616V, 0.585V, and 0.614V, respectively. The fuel cell power densities for Examples 1, 2, 3, and the Comparative Example of the present invention were measured to be 301 mW / cm³. 2 308mW / cm 2 292.5mW / cm 2 307mW / cm 2 At 1.0 A / cm 2 The membrane electrode voltages for Examples 1, 2, 3, and the comparative example of the present invention were measured to be 0.491V, 0.523V, 0.453V, and 0.470V, respectively. The fuel cell power densities for Examples 1, 2, 3, and the comparative example of the present invention were measured to be 491.0 mW / cm³. 2 523.0mW / cm 2 345.0mW / cm 2 470.0mW / cm 2 In the polarization characteristic curves, at the same current density, a higher membrane electrode voltage means a smaller polarization loss in the corresponding fuel cell at that current density, resulting in better overall performance (energy conversion efficiency, lifespan, etc.). Compared to the membrane electrode of the comparative example, the membrane electrode of Example 2 of the present invention has a smaller polarization loss and a higher fuel cell power density, proving that the gradient quaternized cathode catalyst layer provided by the present invention is beneficial to improving the overall performance of the fuel cell. The membrane electrode polarization losses of Examples 1 and 3 are greater than those of Example 2, and even greater than those of the comparative example; and the fuel cell power densities of Examples 1 and 3 are less than those of Example 2, and even less than those of the comparative example. The reason is that, firstly, since the second catalyst layer is disposed between the cathode gas diffusion layer and the first catalyst layer, a large interfacial impedance may be formed between the second catalyst layer and the first catalyst layer, and between the second catalyst layer and the cathode gas diffusion layer in Examples 1 (where the quaternary ammonium group grafting degree of QAPBI in the second catalyst layer is 0%) and Examples 3 (where the quaternary ammonium group grafting degree of QAPBI in the second catalyst layer is 40%) (see [reference]). Figure 4 The high-frequency ohmic impedance (the intersection of the leftmost starting point of each curve and the x-axis) is shown in the figure. Secondly, in the second catalyst layer of Example 1, since no quaternary ammonium groups were introduced, excessive phosphate migration is likely to occur, thus making it impossible to construct a proton transport channel. Thirdly, in the second catalyst layer of Example 3, the high degree of quaternary ammonium group grafting of QAPBI resulted in a relatively dense microstructure in the catalyst layer, which may have blocked some gas diffusion channels, leading to a decrease in performance.

[0118] See Figure 4The impedance spectra of the membrane electrodes prepared in Examples 1, 2, and 3 of the present invention and the comparative example were measured. Figure 4 It can be seen that the high-frequency ohmic impedance of the comparative example (the region with the smaller real impedance in the figure) is the largest, while that of Example 2 is the lowest. This indicates that the introduction of quaternary ammonium groups can anchor phosphoric acid through ion-pair interactions, which is beneficial for constructing stable and efficient proton transport channels and three-phase reaction interfaces, thereby reducing high-frequency ohmic impedance. However, the high-frequency ohmic impedances of Examples 1 and 3 are both greater than that of Example 2. This shows that the introduction of an appropriate amount of quaternary ammonium groups (Example 2) is beneficial for balancing proton conduction efficiency and the stability of the catalyst layer microstructure: on the one hand, the appropriate quaternary ammonium group grafting degree of QAPBI in the second catalyst layer forms a continuous ion channel by anchoring phosphoric acid, reducing the ohmic loss of proton transport; on the other hand, it avoids the catalyst layer structure being too dense due to excessively high quaternary ammonium group grafting degree of QAPBI in the second catalyst layer (Example 3) or the channel being sparse due to excessively low quaternary ammonium group grafting degree (Example 1). The above shows that the grafting degree of quaternary ammonium groups (20%) of QAPBI in the second catalyst layer in Example 2 not only enhances the anchoring effect of phosphoric acid (improves proton conductivity) but also maintains the structure of the catalyst layer (prevents it from being too dense), thereby minimizing the cathode impedance.

[0119] See Figure 5 Cyclic voltammetry curves of the membrane electrodes of Examples 1, 2, and 3 of the present invention and the comparative example were obtained. Calculations showed that the electrochemical active area (ECSA) of Examples 1, 2, and 3 and the comparative example of the present invention was 51.1 m². 2 / g、69.6m 2 / g, 37.9m 2 / g, 65.8m 2 / g. Example 2 showed the highest ECSA, further demonstrating that a well-designed gradient quaternization cathode catalyst layer can achieve efficient proton transport channels and improve the utilization rate of platinum-based catalysts by regulating the distribution of phosphoric acid.

[0120] In summary, the membrane electrode of this invention achieves controlled distribution of phosphoric acid within the catalytic layers through a gradient quaternization design of the cathode bilayer catalytic layers (comprising a first catalytic layer and a second catalytic layer): In the first catalytic layer (near the proton exchange membrane), QAPBI employs highly grafted quaternary ammonium groups, anchoring phosphoric acid molecules through ion-pair interactions, which facilitates uniform phosphoric acid distribution and prevents excessive aggregation of phosphoric acid due to diffusion, thus avoiding coverage of the platinum-based catalyst surface; in the second catalytic layer (away from the proton exchange membrane), QAPBI employs low-grafted quaternary ammonium groups, stabilizing phosphoric acid content through moderate ionic interactions while simultaneously preventing microstructural densification caused by high grafting, thereby preventing blockage of gas diffusion channels. This gradient quaternization structure, by balancing phosphoric acid anchoring and distribution control, constructs a smooth path for proton transport, effectively reducing the ohmic impedance of the membrane electrode and the energy loss of the HT-PEMFC, achieving synergistic optimization of electrochemical reaction efficiency and stability.

[0121] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0122] Although the present invention has been described in detail through the preferred embodiments above, it should be understood that the above description should not be considered as a limitation of the present invention. Various modifications and substitutions to the present invention will be apparent to those skilled in the art after reading the above description. Therefore, the scope of protection of the present invention should be defined by the appended claims.

Claims

1. A membrane electrode, characterized in that, It includes an anode gas diffusion electrode, a proton exchange membrane, and a cathode gas diffusion electrode arranged in sequence; The cathode gas diffusion electrode includes a first catalyst layer and a second catalyst layer; the first catalyst layer is disposed on the side close to the proton exchange membrane; both the first catalyst layer and the second catalyst layer include quaternized polybenzimidazole, a platinum-based catalyst, and polytetrafluoroethylene; wherein, the quaternary ammonium group grafting degree of the quaternized polybenzimidazole in the first catalyst layer is greater than that in the second catalyst layer.

2. The membrane electrode as described in claim 1, characterized in that, The grafting degree of quaternary ammonium groups in the first catalyst layer of quaternized polybenzimidazole is 60% to 100%; the grafting degree of quaternary ammonium groups in the second catalyst layer of quaternized polybenzimidazole is 0% to 40%.

3. The membrane electrode as described in claim 1, characterized in that, The structure formed by the quaternized polybenzimidazole is as follows: The value of n ranges from 60000 to 80000.

4. The membrane electrode as described in claim 1, characterized in that, The total amount of the quaternized polybenzimidazole and polytetrafluoroethylene is 10% to 20% of the mass percentage of the platinum-based catalyst.

5. The membrane electrode as described in claim 1, characterized in that, The mass ratio of the quaternized polybenzimidazole to the polytetrafluoroethylene is 1:3 to 3:

1.

6. The membrane electrode as described in claim 1, characterized in that, The proton exchange membrane is a phosphate-doped polybenzimidazole membrane with a phosphate doping amount of 200% to 400% by mass.

7. A method for preparing a membrane electrode as described in any one of claims 1 to 6, characterized in that, Include: Step 1: Provide a cathode gas diffusion layer, an anode gas diffusion electrode, and a proton exchange membrane; Step 2: Linear aryl ether polybenzimidazole and glycidyltrimethylammonium chloride are dissolved and mixed in a first ratio, and then heated to react and obtain a first solution; linear aryl ether polybenzimidazole and glycidyltrimethylammonium chloride are dissolved and mixed in a second ratio, and then heated to react and obtain a second solution; both the first and second solutions contain quaternized polybenzimidazole, the quaternary ammonium group grafting degree of the quaternized polybenzimidazole in the first solution is 60% to 100%; the quaternary ammonium group grafting degree of the quaternized polybenzimidazole in the second solution is 0% to 40%; Step 3: Dissolve and mix polytetrafluoroethylene, surfactant, and platinum-based catalyst to obtain a dispersion; Step 4: Add the dispersion to the first solution to obtain a first catalyst layer slurry; add the dispersion to the second solution to obtain a second catalyst layer slurry; Step 5: Spray the second catalyst layer slurry onto the surface of the cathode gas diffusion layer to form the second catalyst layer, and spray the first catalyst layer slurry onto the surface of the second catalyst layer to form the first catalyst layer, thereby preparing the cathode gas diffusion electrode; Step 6: The cathode gas diffusion electrode, the proton exchange membrane, and the anode gas diffusion electrode are stacked sequentially, and the membrane electrode is fabricated by hot pressing.

8. The method for preparing a membrane electrode as described in claim 7, characterized in that, In step 2, the first ratio is: the molar ratio of linear aryl ether polybenzimidazole to glycidyl trimethylammonium chloride is 1:0.6 to 1:1; the second ratio is: the molar ratio of linear aryl ether polybenzimidazole to glycidyl trimethylammonium chloride is 1:0 to 1:0.

4.

9. The method for preparing a membrane electrode as described in claim 7, characterized in that, In step 2, the heating reaction temperature is 80℃~100℃, and the reaction time is 10h~15h.

10. A fuel cell, characterized in that, Includes the membrane electrode as described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Low-load gradient high-performance fuel cell membrane electrode and preparation method thereof

    CN115172831A

  • Catalytic layer of high-temperature proton exchange membrane fuel cell and preparation method thereof

    CN119786632A

  • Polymer electrolyte membrane for medium and high temperature, preparation method thereof and high temperature polymer electrolyte membrane fuel cell comprising the same

    KR102238598B1